Interleukin-37: A Link Between COVID-19, Diabetes, and the Black Fungus - Tokajian, Sima; Merhi, Georgi; Al Khoury, Charbel; Nemer, Georges (Frontiers in Microbiology, 2022)
The COVID-19 pandemic involved millions of people and diabetes was identified as an associated comorbidity. Initiation of systemic corticosteroids in patients suffering from severe COVID-19 was associated with lower mortality. A surge of invasive fungal infections of the maxillofacial region, namely mucormycosis, was linked to a deadly infection known as black fungus. Black fungus, diabetes, corticosteroids, and COVID-19 all have a dysregulated immune response in common, which partly could also be attributed to interleukin 37 (IL-37). The use of corticosteroids in diabetic COVID-19 patients, crowded hospitals, and lack of medical oxygen should be carefully considered to reduce COVID-associated secondary infections.